Atypical presentation of complete heart block in children with pediatric inflammatory multisystem syndrome: A case series of two patients - Rishika Mehta; Sanjiban Ghosh; Jayita Das Nandy; Shubhadeep Das; Amitabha Chattopadhyay (Wolters Kluwer Medknow Publications, 2021)
In the midst of the COVID-19 pandemic, we report two cases of children presenting with typical diagnosis of pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) who suffered from complete heart block requiring pacemaker placement which is an unusual presentation of PIMS-TS. We also compared it with the already existing data with similar manifestations. PIMS-TS is reported to occur in children with predominantly gastrointestinal symptoms, hemodynamic instability, and myocardial dysfunction. The implications of development of atrioventricular block during critical illness in PIMS-TS are yet unknown. Both patients had an otherwise normal cardiac structure and had no gastrointestinal symptoms but suffered complete heart block without any other identifiable etiology, both requiring temporary pacemaker placement. While one child recovered completely with medical management, the other child required permanent pacemaker placement. While we cannot be certain that COVID-19 was the cause, complete heart block appeared to be temporally related to COVID-19 infection in both patients, and hence, it is important for pediatricians to be aware of the potential manifestation of this disease.